Propuesta para implementar un manejo Agroecológico en la Finca ´´López`` Barrio Insana del Cantón Sozoranga, Provincia Loja - López Solano, Diana Carolina (2024)
The "Lopez" farm, located in the Insana neighborhood of Sozoranga canton in the province of Loja, is seeking to transition its agricultural methods towards an agroecological model to increase sustainability and productivity. The farm cultivates crops such as corn, beans, faba beans, pigeon peas, coffee, bananas, plantains, oranges, lemons and sugarcane without the use of chemicals. The farm benefits from 30% organic fallow soil and a semi-arid subtropical climate that supports rich biodiversity of both plants and animals. Interviews with the farm owner and neighbors, as well as observation records, were conducted to document farming techniques such as soil preparation, seed use, planting, irrigation, weeding, and fertilization, with the aim of diagnosing the current state of agricultural practices. Based on this diagnosis, a SWOT analysis was used to develop a plan for implementing agroecological practices. Strengths such as the diversity of crops and ancestral knowledge, and weaknesses, such as an insufficient seed production, were identified. The plan includes, organic soil management, crop diversification, integration of sustainable animal production systems, and risk and pest management. The findings highlighted the importance of preserving biodiversity through manual seed selection, manual planting and weeding techniques, use of compost and manure for fertilization, and sprinkler irrigation. Strategies proposed include expanding the agroecological market, promoting of organic products, investing in training, increasing access to capital, integrated pest management, and diversifying income sources.